2017
DOI: 10.1159/000478680
|View full text |Cite
|
Sign up to set email alerts
|

Cold Exposure Differentially Stimulates Angiogenesis in BAT and WAT of Mice: Implication in Adrenergic Activation

Abstract: Background/Aims: To characterize the temporal profile of cold-induced angiogenesis in brown and white adipose tissues of mice in vivo and the temporal changes of angiogenic factors in primary mice brown (BA) and white adipocytes (WA) treated with β3-adrenoceptor agonist (CL316,243) in vitro. Methods: 8-week old male C57BL/6J mice were individually housed in conventional cages under cold exposure (4°C) for 1, 2, 3, 4 and 5 days. Interscapular brown adipose tissue (iBAT), inguinal subcutaneous (sWAT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
5
12
0
Order By: Relevance
“…We examined the vasculatures in the inguinal WAT of the cold-challenged wild-type mice, labeled by the intravenously injected fluorescent Isolectin. In line with previous studies [29] , [30] , there was a significant increase in the vascular density as early as 3 days after the cold challenge ( Figure 3 A). Detailed quantification showed that the density of the vasculatures in the inguinal WAT was 867 ± 73 μm per mm 3 at 0 day, 1551 ± 99 μm per mm 3 at 3 days, 2048 ± 112 μm per mm 3 at 5 days, 2309 ± 138 μm per mm 3 at 7 days, and 2539 ± 126 μm per mm 3 at 10 days after the cold challenge ( Figure 3 B).…”
Section: Resultssupporting
confidence: 92%
“…We examined the vasculatures in the inguinal WAT of the cold-challenged wild-type mice, labeled by the intravenously injected fluorescent Isolectin. In line with previous studies [29] , [30] , there was a significant increase in the vascular density as early as 3 days after the cold challenge ( Figure 3 A). Detailed quantification showed that the density of the vasculatures in the inguinal WAT was 867 ± 73 μm per mm 3 at 0 day, 1551 ± 99 μm per mm 3 at 3 days, 2048 ± 112 μm per mm 3 at 5 days, 2309 ± 138 μm per mm 3 at 7 days, and 2539 ± 126 μm per mm 3 at 10 days after the cold challenge ( Figure 3 B).…”
Section: Resultssupporting
confidence: 92%
“…Our results are in agreement with earlier studies that show transient increase in VEGF in brown adipocytes with BAT activation . The long‐term sympathetic nervous system stimulation either by cold exposure or by β3‐adrenergic agonist administration promote the secretion of VEGF for the transformation of WAT into beige adipose tissue . The VEGF secretion stimulates the proliferation of vascular endothelial cells for adequate expansion of vasculature network in browning adipose tissue.…”
Section: Discussionsupporting
confidence: 93%
“…62,63 The long-term sympathetic nervous system stimulation either by cold exposure or by β3-adrenergic agonist administration promote the secretion of VEGF for the transformation of WAT into beige adipose tissue. [63][64][65] The VEGF secretion stimulates the proliferation of vascular endothelial cells for adequate expansion of vasculature network in browning adipose tissue. The VEGF expression from inguinal beige adipose tissue increased by ~2-fold, which confirms the establishment of adequate vasculature stimulated by β3-adrenergic agonist intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that post mortem visualization of the I-BAT vessels gives better results compared to in vivo methods where native adipose 3 BioMed Research International tissue blocks the vessels' resolution (unpublished results). Vascular thickness or density is often studied with regard to the angiogenesis of WAT or BAT [22] or in metabolism studies [23]. Such studies rarely include anatomical details about vascular diameters; rather, they provide only information about vascular density [6].…”
Section: Discussionmentioning
confidence: 99%